2010
DOI: 10.5194/acpd-10-19219-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Technical Note: Propagating correlations in atmospheric inversions using different Kalman update smoothers

Abstract: Propagating correlations between on-line and off-line state variables in the problem of sequential inversion of surface fluxes for atmospheric CH<sub4</sub> is investigated with the fixed-lag Kalman smoother, the fixed-lag ensemble square root Kalman smoother and the fixed-lag square root sigma-point Kalman smoother. The formulae for the fixed-lag Kalman smoother in Bruhwiler et al. (2005) are further developed with a more concise representation of the posterior covariance. Extension to the fi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Extension to including correlations between on-line (variables are still being updated) and off-line (variables that are no longer updated) state variables is straightforward (see Bruhwiler et al, 2005;Tang and Zhuang, 2010). However, for the specific problem in our study, the gain from accounting for such correlation is rather small, as we showed in Tang and Zhuang (2010).…”
Section: The Fixed-lag Interval Constrained Kalman Smoothermentioning
confidence: 78%
See 4 more Smart Citations
“…Extension to including correlations between on-line (variables are still being updated) and off-line (variables that are no longer updated) state variables is straightforward (see Bruhwiler et al, 2005;Tang and Zhuang, 2010). However, for the specific problem in our study, the gain from accounting for such correlation is rather small, as we showed in Tang and Zhuang (2010).…”
Section: The Fixed-lag Interval Constrained Kalman Smoothermentioning
confidence: 78%
“…Eq. (8) is solved iteratively with the active set method (Murty, 1988), just as documented in Tang and Zhuang (2010). When a set of active constraints are identified, the constraints are set to equality, such that c(s…”
Section: The Fixed-lag Interval Constrained Kalman Smoothermentioning
confidence: 99%
See 3 more Smart Citations